Solid self-nanoemulsifying drug delivery system (S-SNEDDS) for oral delivery of glimepiride: development and antidiabetic activity in albino rabbits. (June 2015) - Mohd, Abdul Bari; Sanka, Krishna; Bandi, Srikanth; Diwan, Prakash V.; Shastri, Nalini
Abstract: Context : This study presents novel self-nanoemulsifying drug delivery system potential of oral delivering which leads poorly aqueous soluble drug glimepiride. Objective : The objective of this study was to prepare solid self-nanoemulsifying drug delivery system (S-SNEDDS) for the improved oral delivery of glimepiride and to evaluate its therapeutic efficacy in albino rabbits. Results and discussion : The droplet size analyses revealed a droplet size of less than 200 nm. The solid state characterization of S-SNEDDS by scanning electron microscopy (SEM), X-ray powder diffraction and differential scanning calorimetry (DSC) revealed the absence of crystalline glimepiride in the S-SNEDDS. The in vitro dissolution studies revealed that the significant improvement in glimepiride release characteristics. The effect of S-SNEDDS on therapeutic efficacy of glimepride was assessed in albino rabbits by monitoring blood glucose levels and compared with free drug suspension, L-SNEDDS. The S-SNEDDS showed significant ( p  < 0.05) increase in in vitro drug release and therapeutic efficacy as compared with free drug. Conclusion : This study demonstrated that S-SNEDDS is a promising novel drug delivery system of glimepride to enhance oral delivery.